Pelatihan Keterampilan Pengelasan GTAW Berbasis Pembelajaran Cybernetic Pada Siswa Teknik Pengelasan SMK 8 Pinrang - Aqsha, Ismail; Nur, Hamzah; Rasyid, Ramli; Fadillah, Nur; Hadryanti, Hadryanti (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
The GTAW welding skills training based on cybernetic learning at SMK Negeri 8 Pinrang was implemented to enhance the quality of teaching and welding competencies, particularly for students in the light vehicle engineering program. Limited availability of welding machines and equipment at the school has restricted students’ opportunities for practice; therefore, the training was designed using practical and communicative methods to ensure accessibility and comprehension. The implementation stages included observation to identify partner problems, program socialization, cybernetic-based training, application of welding technology media, and mentoring with evaluation of welding products. Students received theoretical knowledge of GTAW welding through digital modules covering machine operation, tools and materials, welding procedures, interpretation of technical drawings, and analysis of welding defects. After mastering the theory, students engaged in welding practice through simulation applications, enabling independent skill development. The cybernetic learning model facilitated the integration of theory and practice by utilizing digital technology, encouraging active participation and structured learning. This training is expected to strengthen students’ GTAW welding competencies at SMK Negeri 8 Pinrang, providing them with essential skills to compete in the workforce and industrial sector.